Blessings as a validity indicator of attaining truth in research - Ismail, Nor Hanani (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2017)
Blessings refer to the cause of a good outcome, and is said to be associated with the truth. In research, validity refers to the truth. Indicator is a tool that can be used to measure the achievement of a goal. This paper has two main objectives. First, to analyze the concept of blessings in Islam. Second, to formulate blessings as a validity indicator in research. This paper aims to address both of these issues through textual analysis of some literatures. For the first issue, this paper discusses the views of Islamic scholars concerning the concept of blessings in Islam. For the second issue, the findings sum up that blessings can be used as the indicator of validity in research.